2019
DOI: 10.1149/2.0181913jes
|View full text |Cite
|
Sign up to set email alerts
|

Bromide Ion as a Leveler for High-Speed TSV Filling

Abstract: Organic levelers have been essential additives for Cu electrodeposition to achieve defect-free filling of through-silicon vias (TSVs). They selectively inhibit Cu deposition on top of TSVs, avoiding the occlusion of TSV openings and concentrating Cu deposition inside the TSVs. We recently reported that iodide ions (I − ) can act as an inorganic leveler to induce defect-free TSV filling. However, it was found that I − considerably decreased the efficiency of Cu electrodeposition because of the formation of an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…The layer of the PEG-halide ions formed on the Cu surface can suppress Cu electrodeposition by physically obstructing the Cu ions from approaching the electrode surface, and its suppression ability depends on the type of halide ions. [30][31][32] It was reported that the suppression strength of PEG and halide ions was in the order of Cl -< Br -< Iat the same concentration of halide ions. 31 In this study, we adopted a considerably low concentration of PEG (5 μM) to obtain the suppression breakdown behavior by enhancing the effect of mass transport on the surface coverage of the suppression layers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The layer of the PEG-halide ions formed on the Cu surface can suppress Cu electrodeposition by physically obstructing the Cu ions from approaching the electrode surface, and its suppression ability depends on the type of halide ions. [30][31][32] It was reported that the suppression strength of PEG and halide ions was in the order of Cl -< Br -< Iat the same concentration of halide ions. 31 In this study, we adopted a considerably low concentration of PEG (5 μM) to obtain the suppression breakdown behavior by enhancing the effect of mass transport on the surface coverage of the suppression layers.…”
Section: Resultsmentioning
confidence: 99%
“…35,36,39 We previously reported that the suppression strength of PEG and TSV filling performance can be modulated by halide ions. 23,[30][31][32] The suppression effect increased in the order of Cl − < Br − < I -, and we speculated that Cland Brformed PEG-Clor PEG-Brlayers on the Cu surface, whereas Iformed CuI. Hence, we hypothesized that if the suppression strength can be enhanced by replacing Clwith Bror I -, then PEG-halide ion layers can potentially induce bottomup filling by establishing passive-active regions for Cu electrodeposition.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Kim et al [52] showed that by adding thiourea to the suppressor, PEG-PEG-SPS-I − , the filling time is halved. In addition, Sung et al [53] found out that the reduction in efficiency of the electroplating method occurs when unstable CuI exists at the suppressing layer. To prevent the formation of CuI, they replaced an iodine ion in PEG-PEG-SPS-I − to bromine ion and made PEG-PEG-SPS-Br − .…”
Section: Tsv Fillingmentioning
confidence: 99%
“…Many studies have been conducted on the behavior of additives and their growth mechanisms; however, various additives are still being developed for copper electrodeposition. [19][20][21][22][23][24] In the case of nickel, one of the iron group metals, there have also been many studies on additives for superconformal filling. Polyethyleneimine (PEI) and benzimidazole derivatives, such as 2-mercaptobenzimidazole (MBI) and 2-mercapto-5-benzimidazolesulfonic acid (MBIS), were shown to yield void-free feature filling.…”
mentioning
confidence: 99%